De l’incessante inquiétude à la quête du bonheur - Natália Alves (Carnets)
The journey towards a faraway and unknown destination is a constant in dhôtelian works as if characters had mandatorily a path to cover before finding bliss in an elsewhere, which in fact, is not one. We recognise that André Dhôtel has the intention to unveil the world by the travel, the wandering, and the nature by the walk. In addition to the wish to leave their native land, it is common that characters experience a strong inner pulse that encourages them to run away from their everyday life. We propose to approach the dhôtelian poetic of the wandering in the works La Maison du bout du Monde, L’île aux oiseaux de fer and Un Adieu, mille adieux where we find the need to leave in adventure in the quest of an ideal, a bliss that seems lost.